Collateral benefits from a school‐readiness intervention on breastfeeding: A cross‐domain impact evaluation - Elizabeth B. Miller; Mackenzie D. M. Whipps; Debra L. Bogen; Pamela A. Morris; Alan L. Mendelsohn; Daniel S. Shaw; Rachel S. Gross (Wiley, 2023)
Abstract This study evaluated the collateral, or unanticipated, impacts of Smart Beginnings (SB), a two‐site, tiered intervention designed to promote responsive parenting and school readiness, on breastfeeding intensity in a low‐income sample. Impact analyses for the SB intervention were conducted using an intent‐to‐treat design leveraging a two‐arm random assignment structure. Mothers assigned to the SB intervention group were more than three times more likely to give breastmilk as the only milk source at infant age 6 months than mothers assigned to the control group at one site, an effect not evident at the other study site. As development and growth are the two most salient domains of child health, understanding how interventions impact subsequent parenting practices across both domains is critical to address long‐term economic and racial/ethnic disparities. Implications of the findings are discussed for improving the efficacy of interventions based on paediatric primary care.